On Some Types of Functions in Nonstandard Analysis - Hamad, Ibrahim O.; Jumha, Sebar H. (Science Journal of University of Zakho, 2016)
In this paper, by using some nonstandard concepts given by Robinson and axiomatized by Nelson we study the behavior of functions defined on a discrete intervals, whose points are of infinitesimal distances. This study leads to introduce and define some new types of functions in nonstandard analysis and we get some nonstandard results for different nonstandard values (infinitesimals, infinitely close, unlimited …).
Keywords: Nonstandard Analysis; Limited Function; Continuity; s-Continuity; g-Continuity